Partial differential equations : classical theory with a modern touch - Nandakumaran, A. K.; Datti, P. S. (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
"The aim of the present book is to introduce the fundamental topics in a classical way as in any first book on PDE. The authors have demonstrated the basic topics in such a way that the doors of the modern theory are open to interested readers. For example, after the introduction to method of characteristics for first order equations, immediately the importance of introducing the notion of weak solutions to two important class of first order equations, namely conservation laws and Hamilton-Jacobi equations, is discussed. Almost all the chapters cover something about the modern topics. This is the modern touch that the authors have envisaged and decided to put in the title. Also included are many exercises in most of the chapters. These will help students to get a better insight of the subject. Hints or answers are provided to some selected exercises"--
First-order partial differential equations : method of characteristics -- Hamilton-Jacobi equation -- Conservation laws -- Classification of second-order equations -- Laplace and Poisson equations -- Heat equation -- One-dimensional wave equation -- Wave equation in higher dimensions -- Cauchy-Kovalevsky theorem and its generalization -- A peep into weak derivatives, Sobolev spaces and weak formulation.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Differential equations, Partial -- Textbooks